Предмет: Алгебра,
автор: ursatiy2008
Вычислите: (-8,8-(-3,1)+2,2+(-5,4)-1)*(-10)
Ответы
Автор ответа:
2
Объяснение:
_______________________________
Приложения:
Автор ответа:
1
Ответ:79
Объяснение:(-8,8-(-3,1)+2,2+(-5,4)-1)*(-10)=-8,8+3,1+2,2+(-5,4-1)*(-10)=-3,5+(-4,4)*(-10)=-7,9×(-10)=79 так как минус на минус плюс
Приложения:
Похожие вопросы
Предмет: Русский язык,
автор: egkovalev2006
Предмет: Другие предметы,
автор: 89281134034
Предмет: Русский язык,
автор: xedice20161
Предмет: Английский язык,
автор: аскар51